2007
DOI: 10.1016/j.vph.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential contributions of alpha-1 and alpha-2 adrenoceptors to vasoconstriction in mesenteric arteries and veins of normal and hypertensive mice

Abstract: Mesenteric veins are more sensitive than arteries to the constrictor effects of sympathetic nerve stimulation and α-adrenergic receptor agonists. In the present study, we tested the hypothesis that α 2 -adrenergic receptors (α 2 -ARs) contribute to in vitro agonist-induced constriction in veins but not arteries and that α 2 -AR function is down-regulated in mesenteric arteries and veins in deoxycorticosterone acetate-salt (DOCA-salt) hypertension. Norepinephrine (NE) concentrationresponse curves were similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(38 reference statements)
0
11
0
1
Order By: Relevance
“…Therefore, we studied postjunctional mechanisms that could contribute to the enhanced adrenergic reactivity of mesenteric veins in vitro . Previous work suggested that α 2 -adrenoceptors contribute to norepinephrine-induced constrictions of murine mesenteric veins but not arteries (Perez-Rivera et al, 2007). This was confirmed in the present study where we showed that yohimbine inhibits norepinephrine-mediated constriction of veins but not arteries.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, we studied postjunctional mechanisms that could contribute to the enhanced adrenergic reactivity of mesenteric veins in vitro . Previous work suggested that α 2 -adrenoceptors contribute to norepinephrine-induced constrictions of murine mesenteric veins but not arteries (Perez-Rivera et al, 2007). This was confirmed in the present study where we showed that yohimbine inhibits norepinephrine-mediated constriction of veins but not arteries.…”
Section: Discussionmentioning
confidence: 98%
“…This might be due to artery-vein differences in α-adrenoceptor expression. α 2 -Adrenoceptors potentiate constrictions mediated by α 1 -adrenoceptors in mesenteric veins but not arteries (Perez-Rivera et al, 2007) confirming that α 2 -adrenoceptors play a more prominent role constriction of veins than arteries (Flavahan et al, 1984, Ruffolo, 1986, Patel et al, 1981). A direct coupling between α 1 - and α 2 -adrenoceptors may mediate the functional interaction as occurs in the cauda epididymis (Haynes and Hill, 1996) and glial cells (Wilson and Minneman 1991).…”
Section: Introductionmentioning
confidence: 87%
“…It is widely accepted that norepinephrine is the neurotransmitter for sympathetic adrenergic nerves and activates α 1 -and α 2 -adrenoceptors. In the male mouse mesenteric artery, but not vein, norepinephrine has been shown to cause vasoconstriction via activation through mainly postsynaptic α 1 -adrenoceptors (22). Therefore, it is likely that the PNS-induced vasoconstrictor response is mainly mediated by postsynaptic α 1 -adrenoceptors, which are activated by norepinephrine released from adrenergic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Once released, noradrenaline can act on a variety of receptors on the vascular smooth muscle cells. Previous in vitro studies have found contractile responses to be mediated by activation of the α 1 adrenoceptor in mesenteric arteries and both α 1 and α 2 adrenoceptors in the mesenteric vein (Perez-Rivera et al, 2007). These adrenoceptors are G-protein linked receptors that are coupled to an intracellular increase of inositol 1,4,5-triphosphate (IP3).…”
Section: Vascular Tonus Regulation and Physiology In Mesenteric Vesselsmentioning
confidence: 99%